Descriptive Overview of Iron (Fe) Tablet Compliance Levels Among Pregnant Women at Sangkrah Health Center - Alya' Fatin Ramadhani; Anjar Nurrohmah (OVUM : Journal of Midwifery and Health Sciences, 2026)
Maternal Mortality Rate in Surakarta City increased to 41.04 per 100,000 live births in 2024, with anemia identified as a primary medical cause. Achieving the 2030 Sustainable Development Goals depends heavily on controlling gestational anemia. Sangkrah Health Center records the second-highest number of anemia cases (72 cases), indicating a gap between 100% iron (Fe) tablet distribution and actual consumption rates. Compliance is crucial to prevent complications but remains hindered by maternal characteristics. Objective: This study is designed to provide an overview of the respondents' characteristic profiles and their level of compliance in consuming Fe supplements. Using a descriptive quantitative design, this study involved 74 pregnant women in their second and third trimesters, selected through purposive sampling. Results: Most respondents were aged 21-34 years (78.4%), had high school education (60.8%), were multigravida (55.4%), and were unemployed (75.7%). Regarding compliance, 55 respondents (74.3%) were compliant, while 19 (25.7%) were non-compliant due to forgetfulness and side effects. Conclusion: Most pregnant women are compliant; however, the non-compliant group requires intensive intervention. Puskesmas should improve counseling frequency and utilize digital monitoring to bridge the gap between distribution and consumption.